Flexible graphite bipolar plate and method of making and using same

CN120999031BActive Publication Date: 2026-11-03FOSHAN XIANHU LAB
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202511008579.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-07-22
Publication Date
2026-11-03
Estimated Expiration
2045-07-22

AI Technical Summary

Technical Problem

Existing technologies struggle to achieve synergistic optimization of the strength, conductivity, and sealing properties of flexible graphite bipolar plates in flow batteries, leading to issues such as assembly brittleness, high ohmic losses, and electrolyte cross-contamination.

Method used

Flexible graphite bipolar plates were prepared by using a nanocomposite impregnating agent of surface-functionalized carbon nanotubes and epoxy resin, combined with a vacuum-pressure impregnation process, forming a three-dimensional continuous conductive network and deeply filling the graphite pores.

Benefits of technology

It significantly improves the bending strength and volume conductivity of bipolar plates, reduces surface resistivity and helium permeability, and solves the problems of assembly brittleness and electrolyte cross-permeation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120999031B_ABST
    Figure CN120999031B_ABST
Patent Text Reader

Abstract

The application relates to the technical field of key components of liquid flow batteries, and particularly discloses a flexible graphite bipolar plate and a preparation method and application thereof. The flexible graphite bipolar plate comprises a flexible graphite matrix and a nano-composite impregnating agent filled in pores of the flexible graphite matrix; components of the nano-composite impregnating agent comprise: an epoxy resin, surface-functionalized carbon nanotubes, a curing agent, a dispersing agent and an active diluent; the surface-functionalized carbon nanotubes are carboxylated. Through synergistic reinforcement of the functionalized carbon nanotubes and the epoxy resin, the bending strength of the bipolar plate is greatly improved, and the fracture toughness is significantly enhanced, thus completely solving the brittle fracture problem of the graphite bipolar plate assembly; the functionalized carbon nanotubes form a three-dimensional continuous conductive network in the matrix, the surface resistance of the bipolar plate is greatly reduced, and the volume conductivity is obviously increased, so that the ohmic loss of the battery stack is reduced; a vacuum-pressure combined impregnation process ensures that the nano-composite agent deeply fills the graphite pores, significantly reduces the helium permeability, and completely blocks the cross penetration of the electrolyte.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the technical field of key components of flow batteries, specifically to a flexible graphite bipolar plate, its preparation method, and its application. Background Technology

[0002] Flow battery bipolar plates need to possess high conductivity, strong corrosion resistance, and reliable sealing. While traditional graphite plates are conductive and corrosion-resistant, their inherent brittleness leads to a cracking rate exceeding 30% during assembly, especially when the thickness exceeds 3mm, significantly exacerbating ohmic losses. Flexible graphite paper or felt can partially alleviate the brittleness problem, but their high porosity of 20-60% can cause electrolyte cross-contamination, with measured helium permeability exceeding 10%. -4 cm 2 / s, must rely on resin impregnation to achieve a seal.

[0003] To balance sealing and conductivity requirements, existing technologies employ epoxy resin modification impregnation: adding conductive fillers such as carbon black can reduce the sheet resistance to 15-25 mΩ·cm, but filler sedimentation leads to uneven impregnation and a porosity residue rate exceeding 5%; while using graphene or carbon fiber reinforcement can increase the flexural strength to 50 MPa, the sheet resistance is still higher than 20 mΩ·cm; and the pure resin impregnation scheme further degrades the sheet resistance to over 80 mΩ·cm, and resin cracking after cycling leads to sealing failure.

[0004] Carbon nanotubes can theoretically enhance both mechanical and electrical properties simultaneously, but their practical applications face three major bottlenecks: First, the specific surface area of ​​carbon nanotubes exceeds 200 m² / g. 2 / g, it is extremely easy to agglomerate into bundles, and its dispersion stability in epoxy resin is less than 24 hours; secondly, when more than 2 parts by weight of carbon nanotubes are added, the viscosity of the system increases sharply to more than 2000mPa·s, which cannot fully penetrate the graphite matrix with a thickness greater than 1mm; thirdly, the bonding strength between non-functionalized carbon nanotubes and resin interface is less than 10Mpa, and it is easy to delaminate and peel off under thermal cycling stress.

[0005] In summary, significant gaps remain in current technology: no solution can simultaneously achieve a sheet resistivity ≤10mΩ·cm (ensuring energy efficiency above 85%), a bending strength ≥45MPa (suitable for compact battery stack assembly), and a helium permeability ≤10 - 10 cm 2 The triple objectives of achieving the goal of completely blocking electrolyte cross-contamination require breakthrough innovations in materials and processes. Therefore, it is necessary to provide a flexible graphite bipolar plate, its preparation method, and its application. Summary of the Invention

[0006] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, the present invention proposes a flexible graphite bipolar plate and its preparation method and application, so as to solve the technical contradiction that it is difficult to optimize strength, conductivity and sealing performance in a coordinated manner.

[0007] A first aspect of the present invention provides a flexible graphite bipolar plate.

[0008] Specifically, this includes a flexible graphite matrix and a nanocomposite impregnating agent filling its pores;

[0009] The components of the nanocomposite impregnating agent include: epoxy resin, surface-functionalized carbon nanotubes, curing agent, dispersant, and reactive diluent;

[0010] The surface-functionalized carbon nanotubes are carboxylated.

[0011] Preferably, the components of the nanocomposite impregnating agent, by weight, include: 90-110 parts epoxy resin, 1-4 parts surface-functionalized carbon nanotubes, 20-40 parts curing agent, 0.1-2 parts dispersant, and 5-15 parts reactive diluent.

[0012] More preferably, the components of the nanocomposite impregnating agent, by weight, include: 95-105 parts epoxy resin, 2-4 parts surface-functionalized carbon nanotubes, 25-35 parts curing agent, 1-2 parts dispersant, and 10-15 parts reactive diluent.

[0013] More preferably, the components of the nanocomposite impregnating agent, by weight, include: 100 parts epoxy resin, 3 parts surface-functionalized carbon nanotubes, 30 parts curing agent, 1 part dispersant, and 10 parts reactive diluent.

[0014] Preferably, the epoxy resin comprises bisphenol A type epoxy resin.

[0015] Preferably, the epoxy resin has a viscosity of 100–2000 mPa·s at 25°C.

[0016] Preferably, the surface-functionalized carbon nanotubes have a length of 10–50 μm, a diameter of 10–20 nm, and an aspect ratio ≥500.

[0017] Preferably, the curing agent includes at least one of alicyclic amine curing agents and acid anhydride curing agents.

[0018] Preferably, the dispersant comprises a nonionic polyether-modified siloxane.

[0019] Preferably, the active diluent includes at least one of phenyl glycidyl ether and butyl glycidyl ether.

[0020] A second aspect of the present invention provides a method for preparing a flexible graphite bipolar plate.

[0021] Specifically, the preparation method of flexible graphite bipolar plates includes the following steps:

[0022] Step S1, Flexible graphite substrate pretreatment: The flexible graphite substrate is activated by plasma cleaning or acid washing to obtain a pretreated flexible graphite substrate.

[0023] Step S2, preparation of nanocomposite impregnating agent: surface-functionalized carbon nanotubes are added to an active diluent containing a dispersant, and then ultrasonically treated and dispersed by high-speed shearing to obtain a pre-dispersed slurry; the pre-dispersed slurry is mixed with epoxy resin, and the mixture after grinding is added to a curing agent and stirred, and then vacuum degassed to obtain a nanocomposite impregnating agent;

[0024] Step S3, combined impregnation: The flexible graphite matrix pretreated in step S1 is immersed in the nanocomposite impregnating agent obtained in step S2. In the vacuum stage, the vacuum is first drawn to ≤10kPa and maintained for 20 to 40 minutes. In the pressure stage, the pressure is increased to 0.5 to 2MPa and maintained for 40 to 80 minutes to obtain the impregnated matrix.

[0025] Step S4, Curing and Molding: Place the impregnated substrate in a mold and cure it under a stepwise temperature increase at a pressure of 5-10 MPa: the first stage is at 80-90℃ for 1-2 hours, and the second stage is at 120-130℃ for 2-4 hours.

[0026] Preferably, in step S2, the power of the ultrasonic treatment is 300-500W and the time is 20-40min.

[0027] More preferably, in step S2, the power of the ultrasonic treatment is 450-500W and the time is 25-35min.

[0028] More preferably, in step S2, the power of the ultrasonic treatment is 500W and the time is 30min.

[0029] Preferably, in step S2, the high-speed shear dispersion rotation speed is 4000-6000 rpm and the time is 40-80 min.

[0030] More preferably, in step S2, the high-speed shear dispersion rotation speed is 5000-6000 rpm and the time is 60-80 min.

[0031] More preferably, in step S2, the high-speed shear dispersion rotation speed is 6000 rpm and the time is 60 min.

[0032] Preferably, in step S2, the viscosity of the ground mixture is ≤500 mPa·s.

[0033] More preferably, in step S2, the viscosity of the ground mixture is ≤480 mPa·s.

[0034] More preferably, in step S2, the viscosity of the ground mixture is 480 mPa·s.

[0035] Preferably, in step S3, combined impregnation: the flexible graphite matrix pretreated in step S1 is immersed in the nanocomposite impregnating agent obtained in step S2. In the vacuum stage, the vacuum is first drawn to ≤8kPa and maintained for 25 to 35 minutes, and in the pressure stage, the pressure is increased to 1.5 to 2MPa and maintained for 50 to 70 minutes to obtain the impregnated matrix.

[0036] In a further preferred embodiment, step S3, combined impregnation: the flexible graphite matrix pretreated in step S1 is immersed in the nanocomposite impregnating agent obtained in step S2. In the vacuum stage, the vacuum is first drawn to 5 kPa and maintained for 30 minutes, and in the pressure stage, the pressure is increased to 1.5 MPa and maintained for 60 minutes to obtain the impregnated matrix.

[0037] Preferably, in step S3, the switching interval between the vacuum stage and the pressure stage is ≤5 min.

[0038] Preferably, in step S4, curing and molding: the impregnated substrate is placed in a mold and cured by step heating under a pressure of 8-10 MPa: the first stage is kept at 85-90℃ for 1.5-2 hours, and the second stage is kept at 125-130℃ for 2-3 hours.

[0039] In a further preferred step, step S4, curing and molding: the impregnated substrate is placed in a mold and cured by step heating under a pressure of 8MPa: the first stage is held at 85℃ for 1.5h, and the second stage is held at 125℃ for 3h.

[0040] A third aspect of the present invention provides an application of a flexible graphite bipolar plate in a vanadium redox flow battery.

[0041] Specifically, the flexible graphite bipolar plate is used to isolate the positive and negative electrode electrolytes.

[0042] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0043] 1. Through the synergistic reinforcement effect of functionalized carbon nanotubes and epoxy resin, the bending strength of bipolar plates is greatly improved and the fracture toughness is significantly enhanced, thus completely solving the problem of brittle fracture in graphite bipolar plate assembly.

[0044] 2. Functionalized carbon nanotubes form a three-dimensional continuous conductive network in the matrix, which significantly reduces the surface resistance of the bipolar plates and significantly increases the volume conductivity, thereby reducing the ohmic loss of the battery stack.

[0045] 3. The vacuum-pressure combined impregnation process ensures that the nanocomposite agent deeply fills the graphite pores, significantly reduces helium permeability, and completely blocks electrolyte cross-permeation. Attached Figure Description

[0046] Figure 1 This is a schematic flowchart of the flexible graphite bipolar plate preparation method in Example 1. Detailed Implementation

[0047] To enable those skilled in the art to more clearly understand the technical solutions described in this invention, the following embodiments are provided for illustration. It should be noted that the following embodiments do not constitute a limitation on the scope of protection claimed by this invention.

[0048] Unless otherwise specified, the raw materials, reagents or devices used in the following examples are available from conventional commercial sources or can be obtained by existing known methods.

[0049] Example 1

[0050] The components of the nanocomposite impregnating agent, by weight, include: 100 parts of epoxy resin E51, 3 parts of surface-functionalized carbon nanotubes (diameter 10-20 nm, length 10-50 μm), 30 parts of curing agent T31, 1 part of dispersant BYK-2150, and 10 parts of phenyl glycidyl ether.

[0051] The carboxylation treatment of surface-functionalized carbon nanotubes includes the following steps:

[0052] 1. Add concentrated sulfuric acid to concentrated nitric acid in a dry three-necked flask (volume ratio of concentrated nitric acid: concentrated sulfuric acid = 3:1), stirring with a magnetic stirrer while adding to ensure even mixing and promote heat dissipation.

[0053] 2. Slowly add the weighed, dried carbon nanotube powder to the cooled mixed acid. Continue stirring to disperse the carbon nanotubes in the acid solution.

[0054] 3. Place the three-necked flask on an oil bath. Install the reflux condenser and circulate cooling water to prevent acid evaporation and loss. Turn on the magnetic stirrer, set an appropriate stirring speed, and slowly raise the temperature to 80°C. Maintain reflux at 80°C for 8 hours to carry out the oxidation reaction.

[0055] 4. After the reaction is complete, turn off the heating and allow the reaction mixture to cool naturally to room temperature.

[0056] 5. Slowly pour the cooled reaction mixture into cold deionized water to dilute the strong acid.

[0057] 6. Use a strong acid-resistant PTFE membrane for vacuum filtration on a Buchner funnel. Wash the filter cake repeatedly with deionized water until the pH of the filtrate is close to neutral. During the washing process, carefully stir the filter cake with a glass rod to aid in the washing.

[0058] The method for preparing flexible graphite bipolar plates includes the following steps:

[0059] Step S1, flexible graphite substrate pretreatment: A flexible graphite plate with a porosity of 40% is selected as the substrate, cut to the target size, and then surface activated by oxygen plasma to enhance its interfacial bonding with the impregnating agent, thus obtaining the pretreated flexible graphite substrate.

[0060] Step S2, preparation of nanocomposite impregnating agent: surface-functionalized carbon nanotubes are added to phenyl glycidyl ether containing dispersant, and ultrasonically treated at 500W for 30min, and high-speed sheared dispersed at 6000rpm for 60min to obtain a pre-dispersed slurry; the pre-dispersed slurry is mixed with epoxy resin E51, and milled with three rollers until the viscosity is 480mPa·s, curing agent T31 is added and stirred, and vacuum degassing is performed to obtain nanocomposite impregnating agent;

[0061] Step S3, combined impregnation: The flexible graphite matrix pretreated in step S1 is immersed in the nanocomposite impregnating agent obtained in step S2. In the vacuum stage, the vacuum is first drawn to 5 kPa and maintained for 30 min to completely remove the gas in the pores; then the pressure is quickly switched to the pressure impregnation stage, the pressure is increased to 1.5 MPa and maintained for 60 min to ensure that the nanocomposite agent deeply fills the pores inside the matrix, and the impregnated matrix is ​​obtained.

[0062] Step S4, Curing and Molding: The impregnated substrate is placed in a mold and cured by step heating under a constant pressure of 8MPa: the first stage is to keep it at 85℃ for 1.5h to complete the initial cross-linking, and the second stage is to keep it at 125℃ for 3h to achieve complete polymerization, finally forming a dense and integrated flexible graphite bipolar plate.

[0063] Comparative Example 1

[0064] The components of the nanocomposite impregnating agent, by weight, include: 100 parts of epoxy resin E51, 3 parts of unfunctionalized carbon nanotubes (diameter 10-20 nm, length 10-50 μm), 30 parts of curing agent T31, 2 parts of dispersant BYK-2150, and 10 parts of phenyl glycidyl ether.

[0065] The method for preparing flexible graphite bipolar plates includes the following steps:

[0066] Step S1, flexible graphite substrate pretreatment: A flexible graphite plate with a porosity of 40% is selected as the substrate, cut to the target size, and then surface activated by oxygen plasma to enhance its interfacial bonding with the impregnating agent, thus obtaining the pretreated flexible graphite substrate.

[0067] Step S2, Preparation of nanocomposite impregnating agent: Unfunctionalized carbon nanotubes are added to phenyl glycidyl ether containing dispersant, and ultrasonically treated at 500W for 30 min, and high-speed sheared at 6000rpm for 60 min to obtain a pre-dispersed slurry; the pre-dispersed slurry is mixed with epoxy resin E51, and milled with three rollers until the viscosity is 620mPa·s, then curing agent T31 is added and stirred, and vacuum degassing is performed to obtain the nanocomposite impregnating agent;

[0068] Step S3, combined impregnation: The flexible graphite matrix pretreated in step S1 is immersed in the nanocomposite impregnating agent obtained in step S2. In the vacuum stage, the vacuum is first drawn to 5 kPa and maintained for 30 min to completely remove the gas in the pores; then the pressure is quickly switched to the pressure impregnation stage, the pressure is increased to 1.8 MPa and maintained for 70 min to ensure that the nanocomposite agent deeply fills the pores inside the matrix, and the impregnated matrix is ​​obtained.

[0069] Step S4, Curing and Molding: The impregnated substrate is placed in a mold and cured by step heating under a constant pressure of 8MPa: the first stage is to keep it at 85℃ for 1.5h to complete the initial cross-linking, and the second stage is to keep it at 125℃ for 3h to achieve complete polymerization, finally forming a dense and integrated flexible graphite bipolar plate.

[0070] Comparative Example 2

[0071] The components of the nanocomposite impregnating agent, by weight, include: 100 parts of epoxy resin E51, 0.5 parts of surface-functionalized carbon nanotubes (diameter 10-20 nm, length 10-50 μm), 30 parts of curing agent T31, 1 part of dispersant BYK-2150, and 15 parts of butyl glycidyl ether.

[0072] The carboxylation treatment of surface-functionalized carbon nanotubes includes the following steps:

[0073] 1. Add concentrated sulfuric acid to concentrated nitric acid in a dry three-necked flask (volume ratio of concentrated nitric acid: concentrated sulfuric acid = 3:1), stirring with a magnetic stirrer while adding to ensure even mixing and promote heat dissipation.

[0074] 2. Slowly add the weighed, dried carbon nanotube powder to the cooled mixed acid. Continue stirring to disperse the carbon nanotubes in the acid solution.

[0075] 3. Place the three-necked flask on an oil bath. Install the reflux condenser and circulate cooling water to prevent acid evaporation and loss. Turn on the magnetic stirrer, set an appropriate stirring speed, and slowly raise the temperature to 80°C. Maintain reflux at 80°C for 8 hours to carry out the oxidation reaction.

[0076] 4. After the reaction is complete, turn off the heating and allow the reaction mixture to cool naturally to room temperature.

[0077] 5. Slowly pour the cooled reaction mixture into cold deionized water to dilute the strong acid.

[0078] 6. Use a strong acid-resistant PTFE membrane for vacuum filtration on a Buchner funnel. Wash the filter cake repeatedly with deionized water until the pH of the filtrate is close to neutral. During the washing process, carefully stir the filter cake with a glass rod to aid in the washing.

[0079] The method for preparing flexible graphite bipolar plates includes the following steps:

[0080] Step S1, flexible graphite substrate pretreatment: A flexible graphite plate with a porosity of 40% is selected as the substrate, cut to the target size, and then surface activated by oxygen plasma to enhance its interfacial bonding with the impregnating agent, thus obtaining the pretreated flexible graphite substrate.

[0081] Step S2, preparation of nanocomposite impregnating agent: surface-functionalized carbon nanotubes are added to butyl glycidyl ether containing dispersant, and ultrasonically treated at 500W for 30min, and high-speed sheared dispersed at 6000rpm for 60min to obtain a pre-dispersed slurry; the pre-dispersed slurry is mixed with epoxy resin E51, and milled with three rollers until the viscosity is 320mPa·s, curing agent T31 is added and stirred, and vacuum degassing is performed to obtain nanocomposite impregnating agent;

[0082] Step S3, combined impregnation: The flexible graphite matrix pretreated in step S1 is immersed in the nanocomposite impregnating agent obtained in step S2. In the vacuum stage, the vacuum is first drawn to 5 kPa and maintained for 30 min to completely remove the gas in the pores; then the pressure is quickly switched to the pressure impregnation stage, the pressure is increased to 0.8 MPa and maintained for 50 min to ensure that the nanocomposite agent deeply fills the pores inside the matrix, and the impregnated matrix is ​​obtained.

[0083] Step S4, Curing and Molding: The impregnated substrate is placed in a mold and cured by step heating under a constant pressure of 8MPa: the first stage is to keep it at 85℃ for 1.5h to complete the initial cross-linking, and the second stage is to keep it at 125℃ for 3h to achieve complete polymerization, finally forming a dense and integrated flexible graphite bipolar plate.

[0084] Comparative Example 3

[0085] The components of the nanocomposite impregnating agent, by weight, include: 100 parts of epoxy resin E51, 5 parts of surface-functionalized carbon nanotubes (diameter 10-20 nm, length 10-50 μm), 30 parts of curing agent T31, and 1 part of dispersant BYK-2150.

[0086] The carboxylation treatment of surface-functionalized carbon nanotubes includes the following steps:

[0087] 1. Add concentrated sulfuric acid to concentrated nitric acid in a dry three-necked flask (volume ratio of concentrated nitric acid: concentrated sulfuric acid = 3:1), stirring with a magnetic stirrer while adding to ensure even mixing and promote heat dissipation.

[0088] 2. Slowly add the weighed, dried carbon nanotube powder to the cooled mixed acid. Continue stirring to disperse the carbon nanotubes in the acid solution.

[0089] 3. Place the three-necked flask on an oil bath. Install the reflux condenser and circulate cooling water to prevent acid evaporation and loss. Turn on the magnetic stirrer, set an appropriate stirring speed, and slowly raise the temperature to 80°C. Maintain reflux at 80°C for 8 hours to carry out the oxidation reaction.

[0090] 4. After the reaction is complete, turn off the heating and allow the reaction mixture to cool naturally to room temperature.

[0091] 5. Slowly pour the cooled reaction mixture into cold deionized water to dilute the strong acid.

[0092] 6. Use a strong acid-resistant PTFE membrane for vacuum filtration on a Buchner funnel. Wash the filter cake repeatedly with deionized water until the pH of the filtrate is close to neutral. During the washing process, carefully stir the filter cake with a glass rod to aid in the washing.

[0093] The method for preparing flexible graphite bipolar plates includes the following steps:

[0094] Step S1, flexible graphite substrate pretreatment: A flexible graphite plate with a porosity of 40% is selected as the substrate, cut to the target size, and then surface activated by oxygen plasma to enhance its interfacial bonding with the impregnating agent, thus obtaining the pretreated flexible graphite substrate.

[0095] Step S2, preparation of nanocomposite impregnating agent: surface-functionalized carbon nanotubes are added to dispersant BYK-2150 without active diluent, and ultrasonically treated at 500W for 30 min, and high-speed sheared at 6000rpm for 60 min to obtain a pre-dispersed slurry; the pre-dispersed slurry is mixed with epoxy resin E51, and milled with three rollers until the viscosity is 950mPa·s, curing agent T31 is added and stirred, and vacuum degassing is performed to obtain nanocomposite impregnating agent;

[0096] Step S3, combined impregnation: The flexible graphite matrix pretreated in step S1 is immersed in the nanocomposite impregnating agent obtained in step S2. In the vacuum stage, the vacuum is first drawn to 5 kPa and maintained for 30 min to completely remove the gas in the pores; then the pressure is quickly switched to the pressure impregnation stage, the pressure is increased to 2 MPa and maintained for 80 min to ensure that the nanocomposite agent deeply fills the pores inside the matrix, and the impregnated matrix is ​​obtained.

[0097] Step S4, Curing and Molding: The impregnated substrate is placed in a mold and cured by step heating under a constant pressure of 0.8MPa: the first stage is to keep it at 85℃ for 1.5h to complete the initial cross-linking, and the second stage is to keep it at 125℃ for 3h to achieve complete polymerization, finally forming a dense and integrated flexible graphite bipolar plate.

[0098] Performance testing:

[0099] Table 1. Physical performance test results of the flexible graphite bipolar plates in Example 1 and Comparative Examples 1-3.

[0100] parameter Example 1 Comparative Example 1 Comparative Example 2 Comparative Example 3 Bending strength (MPa) 46 35 39 51 Surface resistivity (mΩ·cm) 8.5 21.7 12.1 6.2 Helium permeability (cm² / s) <![CDATA[5.3×10 -11 ]]> <![CDATA[2.5×10 -9 ]]> <![CDATA[8.7×10 -11 ]]> <![CDATA[3.1×10 -10 ]]>

[0101] Systematic tests on Examples 1 and Comparative Examples 1-3 showed that the carbon nanotube content range and surface functionalization treatment are key factors determining the performance of bipolar plates. When the carbon nanotube content was 0.5 parts (Comparative Example 2), the flexural strength decreased to 39 MPa (a decrease of 15.2% compared to Example 1), while the sheet resistance increased to 12.1 mΩ·cm (an increase of 42.4%), demonstrating that low carbon nanotube content makes it difficult to construct an effective reinforcing-conductive network. When the carbon nanotube content increased to 5 parts (Comparative Example 3), although the flexural strength increased to 51 MPa (an increase of 10.9% compared to Example 1) and the sheet resistance decreased to 6.2 mΩ·cm (a decrease of 27.1%), the system viscosity surged, leading to insufficient impregnation and a deterioration in helium permeability to 3.1 × 10⁻⁶. -10 The increase in cm² / s (484.9%) reveals the inherent contradiction of excessive carbon nanotubes sacrificing sealing performance. In contrast, Example 1, with 3 parts carbon nanotubes, achieved synergistic optimization of flexural strength of 46 MPa and sheet resistivity of 8.5 mΩ·cm, verifying the necessity of 1–4 parts of surface-functionalized carbon nanotubes.

[0102] The experimental results of Comparative Example 1, using unfunctionalized carbon nanotubes, further demonstrate that surface functionalization is an absolute prerequisite for achieving the desired performance. Its flexural strength (35 MPa) and sheet resistivity (21.7 mΩ·cm) deteriorated by 23.9% and 155% respectively compared to Example 1, while the helium permeability increased to 2.5 × 10⁻⁶. -9The fundamental reason for the low density of cm² / s is that the severe aggregation of non-functionalized carbon nanotubes hinders the mechanical enhancement effect and the formation of a conductive network. This phenomenon confirms the irreplaceable role of carboxylation treatment in achieving strong coupling at the carbon nanotube-resin-graphite three-phase interface through covalent bonding.

[0103] The preferred embodiments of the present invention have been described in detail above. It should be understood that those skilled in the art can make numerous modifications and variations based on the concept of the present invention without creative effort. Therefore, any technical solutions obtained by those skilled in the art through logical analysis, reasoning, or limited experimentation based on the concept of the present invention and on the existing technology should be within the scope of protection defined by the claims.

Claims

1. A flexible graphite bipolar plate, characterized in that, Includes a flexible graphite matrix and a nanocomposite impregnating agent filling its pores; The components of the nanocomposite impregnating agent, by weight, include: 100 parts epoxy resin, 3 parts surface-functionalized carbon nanotubes, 30 parts curing agent, 1 part dispersant, and 10 parts reactive diluent. The surface-functionalized carbon nanotubes are carboxylated.

2. The flexible graphite bipolar plate according to claim 1, characterized in that, The epoxy resin includes bisphenol A type epoxy resin.

3. The flexible graphite bipolar plate according to claim 2, characterized in that, The epoxy resin has a viscosity of 100~2000 mPa·s at 25°C.

4. The flexible graphite bipolar plate according to claim 1, characterized in that, The surface-functionalized carbon nanotubes have a length of 10~50 μm, a diameter of 10~20 nm, and an aspect ratio of ≥500.

5. The flexible graphite bipolar plate according to claim 1, characterized in that, The curing agent includes at least one of alicyclic amine curing agents and acid anhydride curing agents.

6. The flexible graphite bipolar plate according to claim 1, characterized in that, The dispersant includes nonionic polyether-modified siloxane.

7. The method for preparing the flexible graphite bipolar plate according to any one of claims 1 to 6, characterized in that, Includes the following steps: Step S1, flexible graphite substrate pretreatment: The flexible graphite substrate is activated by plasma cleaning or acid washing to obtain a pretreated flexible graphite substrate. Step S2, preparation of nanocomposite impregnating agent: surface-functionalized carbon nanotubes are added to an active diluent containing a dispersant, and then ultrasonically treated and dispersed by high-speed shearing to obtain a pre-dispersed slurry; the pre-dispersed slurry is mixed with epoxy resin, ground, and then a curing agent is added and stirred, followed by vacuum degassing to obtain the nanocomposite impregnating agent; Step S3, combined impregnation: The flexible graphite matrix pretreated in step S1 is immersed in the nanocomposite impregnating agent obtained in step S2. In the vacuum stage, the vacuum is first drawn to ≤10 kPa and maintained for 20~40 minutes. In the pressure stage, the pressure is increased to 0.5~2 MPa and maintained for 40~80 minutes to obtain the impregnated matrix. Step S4, Curing and Molding: Place the impregnated substrate in the mold and cure it under a stepwise temperature increase at a pressure of 5~10 MPa: the first stage is at 80~90℃ for 1~2 h, and the second stage is at 120~130℃ for 2~4 h.

8. The preparation method according to claim 7, characterized in that, In step S3, the switching interval between the vacuum stage and the pressure stage is ≤5 min.

9. The application of the flexible graphite bipolar plate according to any one of claims 1 to 6 in an all-vanadium redox flow battery, characterized in that, The flexible graphite bipolar plate is used to isolate the positive and negative electrode electrolytes.

Citation Information

Patent Citations

  • Graphite-based composite bipolar plate for fuel cell and preparation method thereof

    CN113097521A

  • Carbon-based composite conductive paste, graphite plate and preparation method of graphite plate

    CN113659165A

  • Graphite polar plate, preparation method thereof and fuel cell

    CN119283403A